A quasi-experimental mixed-method pilot study to check the efficacy of the “SOUND” active and passive music-based intervention on mental wellbeing and residual cognition of older people with dementia and dementia professionals’ burnout: a research protocol - Sara Santini,; Merizzi, Alessandra; Caciula, Ioana; Azevedo, Maria Joao; Hera, Albert; Napradean, Lena; Di Rosa, Mirko; Quattrini, Sabrina (Frontiers in Psychology, 2024)
Purpose The SOUND method offers an innovative blended intervention based on music circle-activities and cognitive stimulation approaches which was co-designed by musicians, health professionals, older people with dementia, family caregivers and researchers, for its application in dementia settings. The purpose of the paper is to describe the detailed procedure of the quasi-experimental pilot study. Method The experimental phase of SOUND uses a mixed-method design encompassing qualitative and quantitative observations, cognitive testing, self-report and interviewer-assisted questionnaires to investigate the effectiveness of the intervention for 45 people with dementia and 45 professionals (15 in every study country: Italy, Portugal, Romania). Results The pilot study will be the first implementation of the SOUND intervention aiming to investigate the feasibility and preliminary effects of the method. Conclusion The novelty of SOUND is its multicomponent method, including the most evidenced features for improving the wellbeing of participants.